2014
DOI: 10.1016/j.applthermaleng.2014.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Influences of gas flowing on the features of a helium radio-frequency atmospheric-pressure glow discharge

Abstract: In this paper, a zoning model is employed to investigate the influences of gas flowing on the characteristics of the high-purity helium radio-frequency atmospheric-pressure glow discharge (RF APGD) plasma. The modeling results show that the influences of the gas flowing on the plasma features in the discharge region and the jet region are different. In the discharge region, the heavy-particle temperature decreases with the increase of helium flow rate, while the variations of the electron energy and the specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
1
8
1
Order By: Relevance
“…The rate coefficient data of those reactions are determined by the cross-section data [15]. The electron density and the electron energy density are obtained by solving the continuity equations with drift-diffusion approximation [16][17][18][19]: In formulas (1) and (2), n e and e G represent the electron number density and the electron flux vector; S e is the sum of the source and loss items of the electron number density resulting from chemical reactions; e m and D e represent the electron mobility and the electron diffusion coefficient, which are obtained with the Bolsig+solver [16]; and E is the local electric field vector.…”
Section: Simulation Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The rate coefficient data of those reactions are determined by the cross-section data [15]. The electron density and the electron energy density are obtained by solving the continuity equations with drift-diffusion approximation [16][17][18][19]: In formulas (1) and (2), n e and e G represent the electron number density and the electron flux vector; S e is the sum of the source and loss items of the electron number density resulting from chemical reactions; e m and D e represent the electron mobility and the electron diffusion coefficient, which are obtained with the Bolsig+solver [16]; and E is the local electric field vector.…”
Section: Simulation Modelmentioning
confidence: 99%
“…In formulas (3) and (4), n e and G e represent the electron energy density and the electron energy flux vector, respectively. The three terms on the right-hand side of formula (3) represent the Joule heating and energy transfer due to inelastic and elastic collisions, respectively [18]. The E i e D and K i are the energy loss during the inelastic collision process and the corresponding reaction rate (shown in table 1).…”
Section: Simulation Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous studies, a radio-frequency, atmospheric-pressure glow discharge (RF-APGD) plasma jet using a water-cooled, bare-metallic electrode configuration has been developed for the genome mutation of micro-organisms [1,21]. Our studies showed that the RF-APGD was a uniform glow discharge with no filaments, and the gas temperatures were low and controllable by adjusting the operating conditions appropriately [21][22][23][24]. In this study, by adjusting the RF power input and the temperature of the plasma working gas at the inlet of the plasma generator, the gas temperature of the plasma jet can be controlled at a little bit lower level than the room temperature, which means that the heat accumulation inside the treated samples can be avoided during the plasma treatment process.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, researchers have shown that gas flow has an essential influence on plasma properties, nanoparticle formation, and nanoparticle transport [17][18][19][20][21][22][23]. Cole et al [17] studied nanoparticle formation using a dielectric barrier discharge plasma system.…”
Section: Introductionmentioning
confidence: 99%